Revision of Gymnosophistis Meyrick, 1934 (Lepidoptera: Sesiidae) from East Africa with description of a new species - Bartsch, Daniel (Zootaxa, 2018)
In this study, a revision and redescription of Gymnosophistis Meyrick, 1934 is provided. The type species, G. thyrsodoxa Meyrick, 1934, and a new species, G. staudei sp. nov., occur in Kenya. Females and biology of both species are unknown. Gymnosophistis is placed in Sesiini for the first time, with Alonina Walker, 1856 being most likely the sister group. A lectotype of G. thyrsodoxa is designated.